2018
DOI: 10.1111/nyas.13694
|View full text |Cite
|
Sign up to set email alerts
|

Position of human blood group O(H) and phenotype‐determining enzymes in growth and infectious disease

Abstract: The human ABO(H) blood group phenotypes arise from the evolutionarily oldest genetic system found in primate populations. While the blood group antigen A is considered the ancestral primordial structure, under the selective pressure of life-threatening diseases blood group O(H) came to dominate as the most frequently occurring blood group worldwide. Non-O(H) phenotypes demonstrate impaired formation of adaptive and innate immunoglobulin specificities due to clonal selection and phenotype formation in plasma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 131 publications
(212 reference statements)
0
41
0
2
Order By: Relevance
“…Researchers have presented ndings showing that natural antibodies to human red blood cell type B antigens can directly react with some E. coli strains; therefore in a large-scale retrospective report demonstrating that patients with type B and AB have a higher risk of E. coli-related sepsis than those with type O and A [3]. At the same time, research on the relationship between ABO blood group and malaria also found that the prognosis of patients with blood type O was signi cantly better than that of patients with blood type A [4].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have presented ndings showing that natural antibodies to human red blood cell type B antigens can directly react with some E. coli strains; therefore in a large-scale retrospective report demonstrating that patients with type B and AB have a higher risk of E. coli-related sepsis than those with type O and A [3]. At the same time, research on the relationship between ABO blood group and malaria also found that the prognosis of patients with blood type O was signi cantly better than that of patients with blood type A [4].…”
Section: Introductionmentioning
confidence: 99%
“…After that, numerous adult studies were conducted to evaluate possible relationships between blood groups and various human diseases. 10,13,26,27 As in adult lung diseases, there is also genetic predisposition in BPD. However, BPD is a disease of the developing lung unlike adults.…”
Section: Discussionmentioning
confidence: 99%
“…Blood groups have been shown to play an important role in the development of cardiovascular, infectious, oncologic, endocrine, rheumatologic, and other diseases in various studies conducted in adults. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The effect of blood group on neonatal conditions, especially preterm morbidities, has yet to be determined. The presence of blood group antigen on many cell surfaces may be related to the morbidity in premature infants.…”
Section: Introductionmentioning
confidence: 99%
“…Posteriormente, se realizaron muchos estudios en adultos para evaluar la posible relación entre los grupos sanguíneos y diferentes enfermedades. 10,13,26,27 Como sucede con las enfermedades pulmonares en los adultos, también existe una predisposición genética en la DBP. Sin embargo, a diferencia de las enfermedades en los adultos, la DBP es una enfermedad de los pulmones en desarrollo.…”
Section: Discussionunclassified
“…En diferentes estudios en adultos, se demostró que los grupos sanguíneos cumplen un papel importante en el desarrollo de enfermedades cardiovasculares, infecciosas, oncológicas, endocrinas, reumatológicas y de otros tipos. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Aún se debe determinar el efecto que tiene el grupo sanguíneo en las afecciones neonatales, en especial sobre las morbilidades de los prematuros. La presencia del antígeno del grupo sanguíneo en muchas superficies celulares puede estar relacionada con la morbilidad en los lactantes prematuros.…”
Section: Introductionunclassified